An observational cross-sectional study on the impact of polypharmacy on medication adherence in patients with type 2 diabetes mellitus. - Elango, Gayathri; Muralidas, Athira; Praviraj, Dr. Prasheeta V (Student's Journal of Health Research Africa, 2025)
Background: Polypharmacy is increasingly prevalent among patients with Type 2 Diabetes Mellitus (T2DM) due to frequent comorbidities. While multiple medications may be clinically justified, their cumulative burden can impair adherence, ultimately affecting glycaemic control and long-term outcomes. Objectives: To evaluate the prevalence of polypharmacy and its impact on medication adherence in adult patients diagnosed with T2DM. Methods: This cross-sectional observational study included 100 patients with T2DM attending the outpatient department of a tertiary care hospital. Sociodemographic and clinical data were collected, including the number of medications prescribed. Polypharmacy was defined as the concurrent use of five or more medications. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8). Chi-square test was applied to examine the association between polypharmacy and adherence levels. Results: The majority of participants (54%) were aged 50–69 years, and 57% were male. Polypharmacy was observed in 64% of the study population. The MMAS-8 revealed that 41% of patients had low adherence, 38% moderate, and only 21% high adherence. The mean MMAS score was 5.2 ± 1.7. Patients without polypharmacy demonstrated significantly better adherence: 36.1% showed high adherence versus 12.5% among those with polypharmacy. Conversely, low adherence was more frequent among polypharmacy patients (51.6% vs 22.2%). The association between polypharmacy and poor adherence was statistically significant (p = 0.002). Conclusion: This study highlights a high prevalence of polypharmacy among T2DM patients and a significant inverse relationship with medication adherence. These findings underscore the need for individualized treatment regimens and regular medication reviews to reduce pill burden and improve compliance. Recommendations: Routine medication audits and patient education are essential to minimize unnecessary polypharmacy and promote adherence in diabetic care.